Non-linear dielectric response of layered CuInP2S6 and Cu0.9Ag0.1InP2S6 crystals. Issue 1 (9th December 2020) - Dziaugys, Andrius; Zamaraite, Ilona; Macutkevic, Jan; Jablonskas, Dziugas; Miga, Seweryn; Dec, Jan; Vysochanskii, Yulian; Banys, Juras
Abstract: In this work, we report on the results of the examination of the nonlinear dielectric response of layered ferrielectic CuInP2 S6 and Cu0.9 Ag0.1 InP2 S6 crystals. The temperature behaviour of the nonlinear dielectric properties of ferrielectic CuInP2 S6 and Cu0.9 Ag0.1 InP2 S6 is found to be consistent with Landau theory. The additional peak of the third-order nonlinear susceptibility in these crystals, below the phase transition temperature, is strongly influenced by the electric field amplitude, and it is caused by the ferroelectric domain dynamics. The nonzero value of the second-order susceptibility and the mismatch between the temperatures of linear and third-order susceptibilities indicate that some polarisation exists above the phase transition temperature.